Compressive Strength and Elastic Modulus of Slurry Infiltrated Fiber Concrete (SIFCON) at High Temperature - Ali Mudhafar Hashim; Mohammed Mansour Kadhum (Salehan Institute of Higher Education, 2020)
SIFCON is a special type of fiber reinforced concrete (FRC) with an unattached fiber matrix that gives the composite matrix important tensile properties and, due to its high fiber content, SIFCON also has distinctive and unique ductility and energy absorption properties. Higher temperature resistance is one of the most important parameters affecting the durability and service life of the material. In this research, the compression strength and elastic modulus of Slurry Infiltrated Fiber Concrete (SIFCON) were tested both before and after exposure to high temperatures. Two fire exposure durations of 2 and 3 hours are examined. In addition to room temperatures, three temperature ranges of 400 ° C, 600 ° C and 900 ° C have been introduced. The results of the experiment showed that the compressive strength and elastic modulus decreased after exposure to high temperatures. The drastically reduction of compressive strength took place with increasing temperature above 600 °C. While, the reduction in elastic modulus values is more significant than the decrease in compressive strength at the same fire flame temperatures. The residual compressive strength and elastic modulus at 900 °C were in the range of (52.1% to 59.6%) and (30.6% to 34.1%) respectively.